2018
DOI: 10.1093/ons/opy202
|View full text |Cite
|
Sign up to set email alerts
|

The ANTRACK Technique: Employing a Compliant Balloon or Stent Retriever to Advance a Large-Bore Catheter to an Occlusion During Thrombectomy Procedures in Acute Stroke Patients

Abstract: BACKGROUND Stent retrievers and thrombosuction catheters have become the cornerstones of acute stroke therapy. A large-lumen catheter facilitates the passage of different instruments and the application of greater suction force to clots. However, positioning a flexible thrombosuction or intermediate catheter within a tortuous artery is difficult and time-consuming. OBJECTIVE To evaluate the efficacy and safety of the ANchor T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…However, other facilitative, distal anchoring techniquesincluding coil-anchoring and balloonanchoring etc.mostly for endovascular treatment of giant aneurysms, have been reported earlier (Effendi et al, 2016;Oran et al, 2013;Fargen et al, 2013;Snyder et al, 2010). Also, the use of stent retrievers for advancement of large-bore aspiration catheters through tortuous, proximal vessels in the context of intracranial revascularization has been demonstrated previously (Lin et al, 2019;Singh et al, 2015;Mascitelli et al, 2016) and is continuously applied successfully in the clinical routine. Especially the fortifying experience with low profile stent retrievers in stroke treatment (Kurre et al, 2017), more precisely their outstanding distal stability and low risk profile, inspired us to implement them as exchange platforms in technically otherwise hardly controllable scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…However, other facilitative, distal anchoring techniquesincluding coil-anchoring and balloonanchoring etc.mostly for endovascular treatment of giant aneurysms, have been reported earlier (Effendi et al, 2016;Oran et al, 2013;Fargen et al, 2013;Snyder et al, 2010). Also, the use of stent retrievers for advancement of large-bore aspiration catheters through tortuous, proximal vessels in the context of intracranial revascularization has been demonstrated previously (Lin et al, 2019;Singh et al, 2015;Mascitelli et al, 2016) and is continuously applied successfully in the clinical routine. Especially the fortifying experience with low profile stent retrievers in stroke treatment (Kurre et al, 2017), more precisely their outstanding distal stability and low risk profile, inspired us to implement them as exchange platforms in technically otherwise hardly controllable scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The Scepter XC balloon accommodates a larger 0.014-in. microwire, which provides significant stability to the balloon during navigation of tortuous vessels and distal advancement [13,16]. Furthermore, during the balloon inflation, the 0.014-in.…”
Section: Superiorities Of Scepter XC Balloon For Angioplastymentioning
confidence: 99%
“…The Scepter XC balloon (4x11mm; Microvention, Tustin, CA, USA) is a user-friendly temporary consisting of a dual coaxial lumen attached to a lowinflation pressure-compliant balloon. It has excellent trackability and stability, and the extra-compliant design represents technical advancements in endovascular treatment [13][14][15][16]. Few studies have reported on the feasibility of the Scepter balloon for vasospasm treatment [9,13,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…The Scepter XC balloon accommodates a larger 0.014-inch microwire, which provides significant stability to the balloon during navigation of tortuous vessels and distal advancement. [13,16] Furthermore, during the balloon inflation, the 0.014-inch microwire provided increased stability, which resulted in less slippage along the vessel wall relative to the single lumen balloons that have been used previously. Last, we can use a single balloon for multiple segments with repeated inflation and deflation without the need to replace the balloon.…”
Section: Superiorities Of Scepter XC Balloon For Angioplastymentioning
confidence: 99%
“…It has excellent trackability and stability, and the extracompliant design represents technical advancements in endovascular treatment. [13][14][15][16] Few studies have reported on the feasibility of the Scepter balloon for vasospasm treatment. [13,14,17,9] In this study, we detailed the largest single-center case experience of Scepter XC balloon angioplasty and provided an aggressive protocol to treat vasospasm after aneurysm rupture with remarkable clinical outcomes.…”
mentioning
confidence: 99%